Soft Power Strategy: The Role of Indonesia’s Diplomacy in the Peace Mission to the Russian-Ukraine Conflict - Khoirunnisa, Khoirunnisa; Didi Jubaidi (Papua Journal of Diplomacy and International Relations, 2024)
The conflict between Russia and Ukraine has adversely affected global stability and triggered crises. Indonesia took the initiative to facilitate the peace mission. This study aims to analyze the concept and application of soft power strategies in Indonesia’s diplomacy related to the peace mission in the Russia-Ukraine Conflict. A qualitative explanatory method is used to explain the reasons underlying this move. Data collection was conducted through a literature study, while data analysis used a qualitative approach. Soft Power Theory was used as a theoretical framework to understand how Indonesia uses its power of attraction in diplomacy, while the First Track Diplomacy Concept became the foundation to understand the government’s direct role in resolving conflicts. The results showed that Indonesia used the first line diplomacy instrument as part of its peace mission in the conflict between Russia and Ukraine. This is realized through the use of dialogue, negotiation, and cooperation efforts made by both countries. This is in line with Indonesia’s Soft Power goals which seek to improve security in the external environment through the projection of an image as a peaceful and attractive country.  KEYWORDS Conflict; Indonesian Diplomacy; Russia-Ukraine; Soft Power